2016
DOI: 10.1016/j.conb.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

From regions to connections and networks: new bridges between brain and behavior

Abstract: Connections and interactions among distributed brain areas are increasingly recognized as the basis for cognitive operations and a diverse repertoire of behaviors. Analytic advances have allowed for brain connectivity to be represented and quantified at multiple levels: from single connections to communities and networks. This review traces the trajectory of network neuroscience, focusing on how connectivity patterns can be related to cognition and behavior. As recent initiatives for open science provide acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
140
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(145 citation statements)
references
References 66 publications
5
140
0
Order By: Relevance
“…While numerous studies have focused on elucidating brain connectivity patterns that are shared across people, researchers have also acknowledged the high individual variability in brain struc-15 ture [16,17,18], function [19,20,21,22,23,24], and white matter geometry [25,26]. Motivated by this, the concept of connectome fingerprinting, which characterizes individuals using unique connectivity profiles, has recently drawn significant interest from the neuroscience community [27,28,29,30,31,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…While numerous studies have focused on elucidating brain connectivity patterns that are shared across people, researchers have also acknowledged the high individual variability in brain struc-15 ture [16,17,18], function [19,20,21,22,23,24], and white matter geometry [25,26]. Motivated by this, the concept of connectome fingerprinting, which characterizes individuals using unique connectivity profiles, has recently drawn significant interest from the neuroscience community [27,28,29,30,31,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Early studies described the attentional modulation of neuronal activities within individual sensory modalities, whereas recent studies demonstrated crossmodal links in attention 31,[35][36][37][38][39] and the effects of motor preparation on attentional modulation [40][41][42][43][44][45][46] . Furthermore, in this decade, various neural phenomena of attention have been identified using sophisticated recording and analysis methods such as functional magnetic resonance imaging (fMRI) or magnetoencephalography (MEG) as recording methods, and time-frequency, connectivity, and network analyses as analysis methods [47][48][49][50][51][52][53][54][55] . Other stimulation methods including transcranial magnetic stimulation (TMS), direct/alternate current stimulation (tDCS/tACS)), and random noise stimulation (tRNS) and their combination with other methods are also valuable for examining the causal role of relevant brain regions in attentional processing and for artificially manipulating their activities and functions 56) .…”
Section: Attention In Cognitive Neurosciencementioning
confidence: 99%
“…Despite burgeoning evidences on role of different brain regions, neural networks and neurotransmitters providing explanations for diverse cognitive functions [1] the varying behavioural responses of individuals to similar situations [2] necessitates cautious interpretation of the neurological findings taking into account the psychological prospective of the behaviour. Studying the human brain using a human brain therefore remains the most challenging subject for physiologists, neurologists, neuroscientists and psychologists throughout the world.…”
Section: Introductionmentioning
confidence: 99%